SYSTEM OF ECONOMIC RELATIONS BETWEEN THE PARTICIPANTS OF THE LAND MARKET INFRASTRUCTURE OF UKRAINE - KOTELENETS, A. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The land market must function as an integral part of the overall market of the country - this is an objective necessity. At the same time, land is the spatial basis of the existence of the state and its citizens, a link in the ecosystem that requires close attention from the state to ensure political, economic and environmental security; social protection of the population; protection of historical and cultural foundations of the country and its citizens. Modern state policy of land relations in Ukraine is an important factor in ensuring the effectiveness of various socio-political and economic reforms in modern Ukraine, which affects human culture and social order in the country, ensuring optimal development of its natural and resource potential. Today in Ukraine there is still no comprehensive functional approach to the process of reforming land relations in the context of decentralization of power, the regulatory framework in this area is fragmented and unbalanced. The proposed system of economic relations between the institutions of the land market infrastructure creates transparency in the land ownership market. The formation of land market infrastructure institutions in Ukraine will provide a civilized, organized market in which government agencies control the process of buying and selling land, which reflects the interests of preserving the purpose of the land and guarantee effective use. The functional features of such land market infrastructure institutions as the State Land Bank, the State Agency of Land Resources of Ukraine, the Land Exchange, and the Land Court will contribute to more effective state regulation. The State Land Bank in this system acts as a financial institution of the land market and a state controller for the purchase and sale of land, including mortgage lending secured by land ownership, purchase of land from owners and its sale to agricultural enterprises and farmers to preserve the reclamation system and large crop rotation fields. as well as the creation of a fund for the reproduction of soil fertility on the basis of penalties for violators of agronomic requirements and the environment.